2020
DOI: 10.21037/qims-20-664
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic interchangeability of deep convolutional neural networks reconstructed knee MR images: preliminary experience

Abstract: Background: MRI acceleration using deep learning (DL) convolutional neural networks (CNNs) is a novel technique with great promise. Increasing the number of convolutional layers may allow for more accurate image reconstruction. Studies on evaluating the diagnostic interchangeability of DL reconstructed knee magnetic resonance (MR) images are scarce. The purpose of this study was to develop a deep CNN (DCNN) with an optimal number of layers for accelerating knee magnetic resonance imaging (MRI) acquisition b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…DCNN usually performs well with a larger dataset over a smaller one. TL could be useful in the CNN applications where the dataset is not huge [ 13 ]. For applications with comparatively smaller datasets, the concept of TL utilizes the learned model from large datasets such as ImageNet.…”
Section: Proposed Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…DCNN usually performs well with a larger dataset over a smaller one. TL could be useful in the CNN applications where the dataset is not huge [ 13 ]. For applications with comparatively smaller datasets, the concept of TL utilizes the learned model from large datasets such as ImageNet.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…According to [ 13 ], a DCNN model has been developed for comparing the diagnostic interchangeability and image quality of nonaccelerated images to 15-layered DCNNs or 3-layered CNNs images with the optimal number of layers for a sixfold acceleration of the knee MRI dataset, with the optimal number of layers being three.…”
Section: Related Workmentioning
confidence: 99%
“…4. 21,22 In both of these studies, the deep learning algorithms were trained on retrospectively undersampled k-space from 2D sequences using different types of convolutional neural networks. For AI acceleration techniques, although model training is an iterative process that can be time intensive and computationally demanding, once the model is fully trained, image reconstruction is fast and can be performed without the need for special reconstruction hardware.…”
Section: Emerging Techniquesmentioning
confidence: 99%
“…evolve, these advanced imaging techniques should become more practical in a clinical workflow. 12,17,[21][22][23][24][25][26][27] In this review, we discuss 3D MRI sequences currently available for the knee, as well as the advantages and limitations of 3D MRI relative to routine 2D knee MRI. We also describe emerging techniques for 3D MRI, including acceleration and automated quantification techniques.…”
mentioning
confidence: 99%
“…Ghodrati (17) showed that network training using the perceptual loss function achieved better agreement among radiologist scorings as compared to those networks using L 1 , L 2, or structural similarity (SSIM) objective functions. Subhas (18) demonstrated the feasibility of accelerating knee MRI acquisition 6-fold through the application of a novel CNN architecture with deep layers.…”
Section: Original Articlementioning
confidence: 99%